ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN DAERAH AIR MINUM TIRTA SEGAH KABUPATEN BERAU - Anggita, Maya Osiana (STIE Muhammadiyah Tanjung Redeb, 2019)
The purpose of this research is to find out and analyze the Financial Performance of Liquidity, Profitability, Activity, and Solvency Ratios in Tirta Segah PDAM, Berau Regency. In this study it can be seen that this research method uses quantitative descriptive methods. Based on the results of this study Liquidity Ratios seen from the Current Ratio in 2016 amounted to 317.99, in 2017 amounted to 16.25, and in 2018 amounted to 11.56 seen from the calculation of Current Ratio decreased. Quick Ratio in 2016 amounted to 252.02, in 2017 amounted to 11.12, and in 2018 amounted to 9.62 indicating a tendency to decrease. The profitability ratio can be seen from the Net Profit Margin from 2016 of -0.19, in 2017 of 0.02, and in 2018 of 0.09. Viewed from the ROA in 2016 of -0.08, 2017 of 0.02. And in 2018 the amount is 0.08. Judging from ROE in 2016 -0.08, 2017 amounted to 0.02, and in 2018 amounted to 0.08 this increase was due to an increase in net profit after tax. The activity ratio seen from the Total Assets Turnover from 2016 amounted to 0.44, 2017 amounted to 0.96, and in 2018 amounted to 0.85. This means that the assets and capital turnover every year has decreased while the Working Capital Turnover in 2016 amounted to 1.51, in 2017 amounted to 1.52, and in 2018 amounted to 1.56 assets and capital turnover increased every year. The Solvency Ratio can be seen from Total Debt to Total Assets in 2016 of 0,0009, 2017 of 0.0415, 2018 of 0.0517 while Debt to Equity Ratio seen in 2016 of 0,0009, 2017 of 0.0433 , in 2018 amounting to 0.0545 based on the results of the calculation of the Solvency Ratio shows that every year has increased